CORRELATION BETWEEN MATERNAL DENTAL CARIES AND CARIES IN CHILDREN - Cici Idela; Renidayati; Rizki Sofian (Politeknik Kesehatan Kemenkes RI Jakarta I, 2026)
Background: Mothers play a primary role in their children’s oral health behavior and outcomes. Broader research is needed to evaluate the correlation between maternal caries and children's caries to help determine suitable education. Purpose: This study aims to investigate the correlation between maternal caries and their children’s caries aged 4-7 years. Methods: This study uses a correlation design with a cross-sectional approach. A total of 305 mothers and their children were involved as respondents from seven kindergartens in Bukittinggi City, West Sumatra. The caries evaluation was measured using the DMFT score for the mother and the deft score for the children. The dental caries status was assessed using clinical oral examination form to calculate the DMFT index in mothers and deft in children as numerical variables presented as mean and standard deviation (SD). The correlation analysis test was performed to prove the strength of correlation. Results: The mean maternal DMF index was 11.526 ± 6.178, while the mean children deft index was 7.345 ± 4.609. Although the maternal caries experience was higher, the correlation between maternal and child caries scores was very weak and not statistically significant (r = 0.105; p = 0.112). The findings suggest that maternal caries alone may not as strong predictor of caries in children. Conclusion: The correlation between maternal caries and children’s caries is very weak and poses an indirect influence on caries in children. Strengthening maternal oral health education and promoting preventive dental care are essential strategies for improving children’s oral health outcomes.